Inspiring purpose in high-performance schooling - Heng, Mary Anne (New York : Routledge, 2024)
"Is the world better off because your school is in it? Do you believe schooling has a higher purpose? In Inspiring Purpose in High-Performance Schooling, Mary Anne Heng questions modern-day schooling with its dominant focus on what is efficient and effective in good education and how this is measured. This book critically analyses what really matters in high-performance schooling contexts using Singapore as an example and makes a case for putting purpose at the heart of teaching. Going beyond good education built on evidence-based and reflective practice and the instrumental questions of the "What" and "How" of education, she argues for a view of education as transformation with a deeper purpose that pursues the "Why". Using Singapore as a case example and Israel as a counterpoint, she goes behind the rhetoric of developing passion, curiosity, creativity and other 21st century competencies in high-performance schooling to uncover children's real experiences of school. Based on research using multiple sources, she analyses surveys with Singapore and Israeli adolescents and in-depth individual student interviews, as well as provides insights from rich discussions and extended field-testing with practicing teachers and educational leaders to make an urgent call for a new vision in education for the future of education and society-one that celebrates achievement with larger purpose for a wider world. A valuable and resourceful text for teachers, school leaders, policymakers and graduate students in education programmes, as well as education researchers in the fields of educational leadership and change, curriculum, teaching and learning, and youth purpose"--
What are we doing schools for? -- Why we need to do schools differently: From high-performance schooling to purpose-driven schooling -- Meaning in school and life: Finding one's gifts -- Purpose in school and life: Using one's gifts for others -- Youth purpose portraits and sources of influence -- Big lessons from Singapore and Israel -- Inspiring pathways to purpose: What can educators do?
Keywords: Educational change; Transformative learning; Education -- Aims and objectives; Critical pedagogy; EDUCATION / Leadership